Hadith #3711 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mqatl bin Hyan al-Nbty مقاتل بن حيان النبطي (Sunan Abi Dawud)
Dates were steeped for the Apostel of Allah (ﷺ) in skin which was tied up at the top and had a mouth. What was steeped in the morning he would drink in the evening and what was steeped in the evening he would drink in the morning.
Grade: Sahih